Post-experimental follow-ups—Fade-out versus persistence effects: The Rialto police body-worn camera experiment four years on. (November 2017) - Sutherland, Alex; Ariel, Barak; Farrar, William; De Anda, Randy
Abstract: Purpose: Under certain conditions, experimental treatment effects result in behavioral modifications that persist beyond the study period, at times, even after the interventions are discontinued. On the other hand, there are interventions that generate brief, short-term effects that "fade out" once the manipulation is withdrawn or when the in-study follow-up period is completed. These scenarios are context specific. Methods: This study reports the results from a three-year post-experimental follow-up from the world's first randomized controlled trial of police body-worn cameras. Results: The results show that initial falls in rates of complaints against police and police use of force during arrest were sustained during the four years following the cameras being introduced. Conclusions: The findings suggest that police officers do not become habituated to the effect of the body-worn cameras, and that persistence rather than fade-out effects may characterize this emerging technology.